2016
DOI: 10.2174/1874325001610010309
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelet Rich Plasma (PRP) and Other Biologics for Rotator Cuff Repair

Abstract: Background:Surgical treatment of rotator cuff tears has consistently demonstrated good clinical and functional outcomes. However, in some cases, the rotator cuff fails to heal. While improvements in rotator cuff constructs and biomechanics have been made, the role of biologics to aid healing is currently being investigated.Methods:A selective literature search was performed and personal surgical experiences are reported.Results:Biologic augmentation of rotator cuff repairs can for example be performed wtableit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…PRP and stem cells enhance the regenerative potentials of tendon stem cells [ 12 14 ] and regeneration of torn supraspinatus in preclinical studies [ 15 , 16 ]. Several clinical studies have described PRP-augmented rotator cuff repairs in patients with rotator cuff tears [ 17 , 18 ]. Therefore, regenerative biological treatment will be helpful to restore shoulder function and prevent the progression of tear.…”
Section: Introductionmentioning
confidence: 99%
“…PRP and stem cells enhance the regenerative potentials of tendon stem cells [ 12 14 ] and regeneration of torn supraspinatus in preclinical studies [ 15 , 16 ]. Several clinical studies have described PRP-augmented rotator cuff repairs in patients with rotator cuff tears [ 17 , 18 ]. Therefore, regenerative biological treatment will be helpful to restore shoulder function and prevent the progression of tear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PRP therapy is suggested as an auxiliary therapy in singlerow arthroscopic rotator cuff repair for ameliorated short period of time outcomes [19]. However, several clinical studies have reported contradictory findings in terms of the appropriateness of PRP for rotator cuff tears [20].…”
Section: Use Of Platelet-rich Plasma In Rotator Cuff Injury Treatmentmentioning
confidence: 99%
“…After development of stem cell therapies to assist with RCR and additional clinical results in a human population, a thorough cost-effective analysis is crucial to determine if there is a potential role in RCR. 108…”
Section: Stem Cells: the Early Evidencementioning
confidence: 99%